2017
DOI: 10.20341/gb.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Facies and micromorphology of the Neoproterozoic Upper Diamictite Formation in the Democratic Republic of Congo: new evidence of sediment gravity flow

Abstract: ABSTRACT. The Upper Diamictite Formation of the West Congo Supergroup is a diamictite-dominated succession variously interpreted as a continental tillite, glaciomarinite, and glacially-influenced or non-glacial debrite. This paper presents a detailed macroand microscale analysis of soft-sediment deformation structures in order (1) to resolve the long-standing debate on the genetic origin of the Upper Diamictite Formation, and (2) to constrain the paleoenvironmental conditions during the Marinoan global event. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, recent studies of the WCB have revealed only a minor impact of these glaciations on sedimentation. On the contrary, predominantly extensional tectonic activity controlled basin formation with dolostones (at the base of the Lukala Subgroup) abruptly overlying the Upper Diamictite Formation, formerly considered as a glaciogenic deposit (Eyles and Januszcak, 2007;Delpomdor et al, 2014Delpomdor et al, , 2016Delpomdor et al, , 2017. In this paper, new detailed lithofacies associations, stratigraphic architecture and geochemistry of the C5 Formation point to a paleogeographic setting with a vast shallow back-reef lagoon stretching between a stromatolitic patch reef and a coastal sabkha plain.…”
Section: Introductionmentioning
confidence: 77%
“…However, recent studies of the WCB have revealed only a minor impact of these glaciations on sedimentation. On the contrary, predominantly extensional tectonic activity controlled basin formation with dolostones (at the base of the Lukala Subgroup) abruptly overlying the Upper Diamictite Formation, formerly considered as a glaciogenic deposit (Eyles and Januszcak, 2007;Delpomdor et al, 2014Delpomdor et al, , 2016Delpomdor et al, , 2017. In this paper, new detailed lithofacies associations, stratigraphic architecture and geochemistry of the C5 Formation point to a paleogeographic setting with a vast shallow back-reef lagoon stretching between a stromatolitic patch reef and a coastal sabkha plain.…”
Section: Introductionmentioning
confidence: 77%
“…(). In the light of detailed sedimentological data from Kamoa it seems reasonable to argue that mass flow was a widespread (if not dominant) and diachronous process in peri‐Congolese Katangan rift basins and that such deposits cannot be used in support of a notional pan‐glacial Snowball Earth event (see also Delpomdor & Préat, ; Delpomdor et al ., , ). Regional ice covers whose timing reflect a dominantly tectonic control on basin development and topographic relief are possible but the wealth of sedimentological detail available from deep drilling at Kamoa identifies a distal and weak (if any) glacial influence.…”
Section: Discussionmentioning
confidence: 97%
“…Only a single deposit (the Lower Diamictite Formation of the West-Congo Supergroup, West Congo Belt) has been dated (694 AE 4 Ma; Straathof, 2011) and this age contrasts with the bracket obtained from radiometric dating for the Grand Conglom erat of 765 AE 5 to 735 AE 5 Ma (Key et al, 2001), the maximum age of the Grand Conglom erat obtained from Re-Os dating in the Mwashya Subgroup of 727Á3 AE 4Á9 Ma (Rooney et al, 2015) and also the 757 AE 5 Ma lower limit age obtained for the Chuos Formation of Namibia by Nascimento et al (2016). In the light of detailed sedimentological data from Kamoa it seems reasonable to argue that mass flow was a widespread (if not dominant) and diachronous process in peri-Congolese Katangan rift basins and that such deposits cannot be used in support of a notional pan-glacial Snowball Earth event (see also Delpomdor & Pr eat, 2015;Delpomdor et al, 2016Delpomdor et al, , 2017. Regional ice covers whose timing reflect a dominantly tectonic control on basin development and topographic relief are possible but the wealth of sedimentological detail available from deep drilling at Kamoa identifies a distal and weak (if any) glacial influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This isotopic "event" is followed by a positive excursion in δ 13 C values, which is marked by a rapid marine transgression as a result of extensional tectonic processes directly after the Marinoan-age glaciation event (Halverson et al, 2005;Delpomdor et al, 2016;Caxito et al, 2012;Paula-Santos et al, 2017). Such glaciations are recorded in the Ghaub Formation in Namibia, Jequitaí Formation in Brazil, and periglacial deposition in the Niari Formation in Gabon, stratigraphic-equivalent of the distal gravity deposited sediments in the Upper Diamictite Formation in DRC (Prian et al, 2009;Busfield and Le Heron, 2013;Uhlein et al 2013Uhlein et al , 2016Delpomdor et al, 2016Delpomdor et al, , 2017F. Delpomdor, S. Schröder, A. Préat, P. Lapointe, C. Blanpied Nascimento et al, 2016;Rodler et al, 2017).…”
Section: Stratigraphic Correlationsmentioning
confidence: 99%